День египетского мальчика - Матье Милица Эдвиновна (Ученые России - детям, 2002)
Экземпляры: ф.2 (20160420) / Инвентарный номер: 35488 / Цена: 138.00 / Авт.знак: М 35 / ГРНТИ: 17.82.93 / ББК: 84 (2Рос=Рус)6